NOTARY AUTHORITY IN MAKING AUTHENTIC DEEDS REGARDING COPYRIGHT - R. July Moertiono; Adi Mansar (Jurnal Pembaharuan Hukum, 2022)
The issue of notary authority in the creation of authentic deeds regarding copyright since the authority of DJKI to directly record copyright. However, in the framework of copyright protection, an authentic notary deed is required to give validity to the copyright. The research method used is normative juridical. The results showed that in the Notary Copyright Act is also authorized to make authentic deeds of the copyright field in order to protect copyright works that will then be recorded to DJKI. In the HCAct, notaries have the authority to make authentic deeds of transfer over copyright. Transfer of copyright can be done from the copyright owner to another designated party. However, this transfer does not necessarily get all exclusive rights from the copyright owner. The designated party in the transfer can only get economic rights only. The moral rights to the intellectual property remain owned by the copyright owner. Although in the Act the transfer of copyright is done clearly and in writing either with or without a notary deed, it should be equipped with an authentic deed from a notary. This is based, this transfer of copyright is closely related to the transfer of economic rights, so it takes a deed that has strong legal evidentiary power.